Peran Pemerintah Daerah Kota Bukittinggi dalam Pencegahan Perusakan Kawasan Konservasi Margasatwa Berdasarkan Undang-undang Pemerintahan Daerah: The Role of Bukittinggi Regional Government in Preventing Destruction of Wildlife Conservation Based on Regional Government Law - Elsa Salsabila; Dhany Rahmawan (Reformasi Hukum Trisakti, 2024)
Bukittinggi has a conservation area called Kinantan Wildlife and Cultural Park which must be protected and managed based on the principle of State responsibility, the principle of sustainability, and the principle of justice to prevent the destruction of wildlife conservation areas. The formulation of the problem in this writing is what is the role of the Bukittinggi City Regional Government in preventing the destruction of Wildlife Conservation Areas in its area? And is the role of the Bukittinggi City Regional Government in preventing the destruction of Wildlife Conservation Areas in accordance with Law Number 23 of 2014 concerning Regional Government? The results and conclusions of this research are the role of the Bukittinggi City Regional Government in preventing the destruction of the Margasatwa Conservation Area can be seen from several actions taken, namely as a regulator, supervisor, and organizer. In its implementation in carrying out the role of regional autonomy, the Bukittinggi City Regional Government has been in accordance with the provisions of the applicable laws.